In vitro evaluation of NLS-DTX activity in triple-negative breast cancer - Paiva, Karen Letycia Rodrigues de (2022)
Cancer is one of the most lethal diseases in the world, and the development and improvement of treatments used in cancer therapies are extremely important for a better quality of life for patients. In view of the current problems in drug administration such as low solubility and adverse effects, the activity of a solid lipid nanoparticle containing docetaxel (SLN-DTX), a drug already used in conventional therapies, was evaluated in a cell line (MDA-MB-231) of one of the most aggressive types of breast cancer with the worst prognosis, triple-negative breast cancer. Viability tests indicated that SLN-DTX has a greater dependence on the treatment dose when compared to the free drug, which indicates a more controlled release of the drug, and both reduced viability by around 50% at a concentration of 1 µg/mL after 72 h. Transmission electron microscopy (TEM) and confocal and light microscopy analyses indicated that after treatment the cells enter a mitotic catastrophe, characteristic of antimitotic drugs that usually make cells progress to death or senescence. Cells treated with both DTX and SLN-DTX showed significant inhibition of mobility, 73.6% and 66.5% when treated with SLN-DTX and DTX, respectively, compared to the 11.4% of the control after 72 h, characteristics that are very relevant in tumor development and progression. SLN-DTX demonstrated its great potential as a nanocarrier by maintaining and improving the drug’s action in the MDA-MB-231 cell line.